Neurofibromatosis Type 2 Presenting with Oculomotor Ophthalmoplegia and Distal Myopathy - Jessica Mani Penny Tevaraj; Evelyn Tai Li Min; Raja Azmi Mohd Noor; Azhany Yaakub; Wan Hazabbah Wan Hitam (Case Reports in Ophthalmological Medicine)
Neurofibromatosis type 2 usually presents with bilateral acoustic schwannomas. We highlight the rare presentation of neurofibromatosis initially involving third nerve. A 23-year-old Malay female presented with left eye drooping of the upper lid and limitation of upward movement for 8 years. It was associated with right-sided body weakness, change in voice, and hearing disturbance in the right ear for the past 2 years. On examination, there was mild ptosis and limitation of movement superiorly in the left eye. Both eyes had posterior subcapsular cataract. Fundoscopy showed generalised optic disc swelling in both eyes. She also had palsy of the right vocal cord, as well as the third and eighth nerve. There was wasting of the distal muscles of her right hand, with right-sided decreased muscle power. Pedunculated cutaneous lesions were noted over her body and scalp. MRI revealed bilateral acoustic and trigeminal schwannomas with multiple extra-axial lesions and intradural extramedullary nodules. Patient was diagnosed with neurofibromatosis type 2 and planned for craniotomy and tumour debulking, but she declined treatment. Neurofibromatosis type 2 may uncommonly present with isolated ophthalmoplegia, so a thorough physical examination and a high index of suspicion are required to avoid missing this condition.